2020
DOI: 10.1093/molehr/gaaa052
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two cell-fates: role of the Hippo signaling pathway and transcription factors in early lineage formation in mouse preimplantation embryos

Abstract: Abstract In mammals, the first cell-fate decision occurs during preimplantation embryo development when the inner cell mass (ICM) and trophectoderm (TE) lineages are established. The ICM develops into the embryo proper, while the TE lineage forms the placenta. The underlying molecular mechanisms that govern lineage formation involve cell-to-cell interactions, cell polarisation, cell signaling and transcriptional regulation. In this review, we will discuss the cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 92 publications
0
19
0
Order By: Relevance
“…3f ), we suspected that the differentiation of preimplantation embryos could be regulated by BZW1. Immunofluorescence staining revealed the levels and localization of OCT4, NANOG, and CDX2 proteins, all of which are essential for the differentiation of ICM and TE 27 , 28 . The results suggest that OCT4 and NANOG protein levels decreased in Bzw1 -knockdown embryos with irregular localization during the 8-cell to blastocyst stages, whereas CDX2 was unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3f ), we suspected that the differentiation of preimplantation embryos could be regulated by BZW1. Immunofluorescence staining revealed the levels and localization of OCT4, NANOG, and CDX2 proteins, all of which are essential for the differentiation of ICM and TE 27 , 28 . The results suggest that OCT4 and NANOG protein levels decreased in Bzw1 -knockdown embryos with irregular localization during the 8-cell to blastocyst stages, whereas CDX2 was unaffected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In general, unphosphorylated YAP translocates to the nucleus, whereas phosphorylated YAP undergoes cytoplasmic inactivation [ 11 , 13 , 14 ]. Here we detected YAP only in nuclei in day 6 and day 8 bovine embryos, when using an anti-YAP antibody that recognizes both phosphorylated and unphosphorylated YAP; it is possible that YAP is rapidly removed from the cytoplasm after phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, studies have revealed that the Hippo pathway is involved in follicular activation and follicle growth [ 7 , 8 , 9 ]. In addition, emerging evidence has indicated that the Hippo-YAP signaling pathway also plays an essential role in controlling the expression of the key transcription factors in first-lineage segregation (ICM and TE differentiation) during mouse preimplantation development [ 10 , 11 , 12 , 13 ]. In the cells on the outside of the morula, where the Hippo pathway is inactive, YAP/TAZ remain unphosphorylated and migrate to the nucleus to bind the transcriptional coactivator TEAD4 facilitating Cdx2 expression, and subsequently driving them to a TE fate [ 11 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Malfunctioning of Hippo components has been associated with defects in TE as well as inner cell mass (ICM) specification leading preimplantation developmental arrest [ 23 , 24 ]. Recently, Hippo has been reported to translate positional information into indispensable transcriptional circuits specifying the trophectoderm in preimplantation embryos [ 25 , 26 ]. Molecular orchestration between Hippo and other signaling pathways is imperative to trophectoderm restriction [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%